Halide selective anion recognition by an amide-triazolium axle containing [2]rotaxane. - White, N; Colaço, A; Marques, I; Félix, V; Beer, P (2014)
A new rotaxane containing the 3-amido-phenyl-triazolium group incorporated into the interlocked structure's axle component has been prepared by a chloride anion templated clipping strategy. Proton NMR titration experiments reveal that the interlocked host displays a high degree of halide anion recognition in competitive 1 : 1 CDCl3-CD3OD solvent mixture. Chloride and bromide anions are bound strongly and selectively, with negligible complexation of the larger, more basic oxoanions, acetate and dihydrogen phosphate being observed. Density functional theory calculations on the related axle motifs 3-amido-phenyl-triazolium, pyridinium bis-triazole and pyridinium bis-amide were performed, and indicate that the new rotaxane axle motif displays much weaker oxoanion binding than the pyridinium based systems.